Glacial Isostatic Uplift in the Tibetan Plateau and Surroundings - Shaozhuo Liu; Sigurjón Jónsson (Geophysical Research Letters)
Abstract The Tibetan Plateau and surroundings host the largest number of modern glaciers outside the polar regions. However, the impact of (de)glaciation on present‐day geodetic measurements remains unclear. Using load deformation models, we examine the glacial isostatic uplift in response to (de)glaciation during the last glacial period and since the Little Ice Age. We find that the current glacial isostatic uplift locally exceeds 2.0 mm/yr near some glaciers in the Himalayas, Nyainqentanglha, Pamir, and Tien Shan. In the Nyainqentanglha, this glacial isostatic uplift could otherwise be misinterpreted as tectonic uplift associated with fictitious structures near the Jiali fault, a strike‐slip fault slipping at 2–5 mm/yr. In the Himalayas, the glacial isostatic uplift may contribute to 10%–40% of the observed 5–6 mm/yr geodetic uplift. In the Tien Shan, this ratio is 0%–50%. Therefore, glacial isostatic uplift must be considered when interpreting geodetic measurements in the Tibetan Plateau and surroundings.